Friction and Wear Characteristics of TIG Processed Surface Modified Grey Cast Iron - Pandya, S. N.; Nath, S. K.; Chaudhary, G. P. (Journal of Scientific Research, 2009)
The surface of gray cast iron has been modified by Tungsten Inert Gas (TIG) process. Welding current of magnitude 25, 35, and 45 amperes have been used to melt the surface of gray cast iron. Microstructural characterization, hardness measurement and dry sliding wear tests have been performed on these modified surfaces. It has been observed that increase in welding current caused the microstructure of grey cast iron to be gradually refined. Graphite flakes segregated between interdendritic regions in the as-received grey cast iron have been completely replaced by a uniform distribution of finer graphite flakes in the matrix. Hardness has been found to increase with increase in welding current. Wear resistance of the gray cast iron also increased with increase in the welding current reaching maximum value for 45 amperes. The increased hardness and wear resistance of these modified surfaces have been explained on the basis of microstructural changes occurring at the surfaces of gray cast iron. Keywords: Gray cast iron; Surface modification; TIG process; Dry sliding wear. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.vli3.2577 J. Sci. Res. 1 (3), 516-527 (2009)